EFFECTIVENESS OF NATIONAL ADMINISTRATION SYSTEMS IN IMPLEMENTATION OF PUBLIC SERVICES - Hotmaria Hertawaty Sijabat (ADMIN: Jurnal Administrasi Negara, 2024)
When it comes to the standard of public service, the efficiency of the state administration system is crucial. The role of institutions and supervisory mechanisms in improving effectiveness has a crucial role in enhancing the efficiency of the state administration system. For example, regulatory bodies such as ombudsmen, financial regulators, and government internal regulators can play an important role in ensuring that regulations are implemented properly and effectively. With effective supervisory institutions and mechanisms, it can be expected that public services will become more transparent, accountable, and responsive to the needs of the public. Therefore, coordinated efforts between the government, the supervisory agencies, and civil society are required to ensure the efficacy of state administration in the public service. The research methodology used in this study is library research. The concepts of public administration, state administration, and the relationship between public services and state administration are covered in this study, along with the variables influencing the efficiency of the state administration system and its impact on public service improvement.